Struggling upward : worldly success and the Japanese novel - Van Compernolle, Timothy J., 1968- (Harvard East Asian monographs, 2016)
"Reconsiders the rise of the novel in Japan in the Meiji Era by connecting the genre to new discourses on social mobility, ambition, and success. Situates the modern novel in a larger context of modernity, as a literary form engaged with a rapidly changing society"--